Money's unholy trinity: Devil, trickster, fool. Issue 1 (1st January 2016) - Cameron, Angus
Abstract : This paper argues that traditional associations between money and the devil remain with us – best seen in narratives about the (im)morality of money following the crisis of 2008. However, such eruptions of moral concern about money and finance mask the more fundamental problems of a money economy that these associations sought to articulate in the first place. The fundamentally 'demonic' nature of money is not necessarily either about 'evil', but expresses the ontological insecurities both of money itself and of the social changes it brings about. The paper looks at the long historical association between money and three overlapping 'psychologems' – Trickster, Devil and Fool. It argues that these 'mythic' characters performed an important function in allowing the complexity of money to be articulated and embodied.